Pendidikan Inklusif dalam Toleransi Beragama - Fadilah, Ahmad Arif (TSAQOFAH, 2024)
The discussion on "Inclusive Education in Religious Tolerance" highlights the crucial role of education in shaping an inclusive society that values religious diversity. The concept of inclusive education not only provides an understanding of religious diversity but also instills values of tolerance, mutual respect, and cooperation among students from diverse religious backgrounds. An inclusive learning environment is considered a crucial factor in supporting the formation of character and the development of tolerant attitudes. The implementation of religious values in the context of inclusion, the role of teachers, and the development of inclusive curriculum are the main focus in achieving this goal.